1995
DOI: 10.1159/000236994
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hyposensitization to Nickel Allergy: Preliminary Clinical Results

Abstract: Fifty-one patients presenting a dermatological allergy (erythema, urticaria, angioedema, contact dermatitis) to nickel were treated over 3 years with oral doses of 0.1 ng nickel sulfate per day, following a low-nickel diet. Diagnostic tests comprised patch and oral provocation tests. In 7 cases, the treatment was interrupted because of symptom reactivation, and in 14 cases for other reasons. Among the 30 cases who went through the whole follow-up, symptomatology totally disappeared in 29 cases, and a partial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…edema of the gluteal area and of the major flexures (baboon syndrome) (16)(17) and generalized urticaria (12,(18)(19)(20). Moreover, studies on the histological modifications of the gastrointestinal mucosa have shown a marked inflammatory infiltrate, mainly Iymphoplasmacellular, associated with duodenum villus deformation and deepening of the crypta, in some subjects with delayed allergy to nickel sulfate after oral challenge test (21) and after accidental ingestion of a nickel coin (22).…”
mentioning
confidence: 99%
“…edema of the gluteal area and of the major flexures (baboon syndrome) (16)(17) and generalized urticaria (12,(18)(19)(20). Moreover, studies on the histological modifications of the gastrointestinal mucosa have shown a marked inflammatory infiltrate, mainly Iymphoplasmacellular, associated with duodenum villus deformation and deepening of the crypta, in some subjects with delayed allergy to nickel sulfate after oral challenge test (21) and after accidental ingestion of a nickel coin (22).…”
mentioning
confidence: 99%
“…At present, there is no immunotherapy available for treating type-IV hypersensitivity, however, the fact that people living in close proximity to nickel factories are less prone to develop nickel allergies than a comparable population living at further distances from the same factories, suggest that tolerance induction to nickel may be possible [6]. Likewise, a few immunotherapeutic clinical trials suggested a possible tolerating effect of oral administration of nickel salts [7,9,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…2). When symptoms, such as chronic urticaria or gastrointestinal disorders unrelated to enzymatic deficiencies or to small bowel bacterial overgrowth, do not seem to be related to a single food, the physician should consider a delayed-type allergy to nickel [9], chrome, cobalt or a latex-fruit syndrome [10]. In case of a positive patch test to nickel, chrome or cobalt, patients should avoid foods containing these metals (a positive response is usually seen at least after 4 weeks of the elimination diet).…”
Section: Diagnostic Testsmentioning
confidence: 99%